Hearing loss genes reveal patterns of adaptive evolution at the coding and non-coding levels in mammals - Anabella P. Trigila; Francisco Pisciottano; Lucía F. Franchini (BMC Biology, 2021)
Abstract Background Mammals possess unique hearing capacities that differ significantly from those of the rest of the amniotes. In order to gain insights into the evolution of the mammalian inner ear, we aim to identify the set of genetic changes and the evolutionary forces that underlie this process. We hypothesize that genes that impair hearing when mutated in humans or in mice (hearing loss (HL) genes) must play important roles in the development and physiology of the inner ear and may have been targets of selective forces across the evolution of mammals. Additionally, we investigated if these HL genes underwent a human-specific evolutionary process that could underlie the evolution of phenotypic traits that characterize human hearing. Results We compiled a dataset of HL genes including non-syndromic deafness genes identified by genetic screenings in humans and mice. We found that many genes including those required for the normal function of the inner ear such as LOXHD1, TMC1, OTOF, CDH23, and PCDH15 show strong signatures of positive selection. We also found numerous noncoding accelerated regions in HL genes, and among them, we identified active transcriptional enhancers through functional enhancer assays in transgenic zebrafish. Conclusions Our results indicate that the key inner ear genes and regulatory regions underwent adaptive evolution in the basal branch of mammals and along the human-specific branch, suggesting that they could have played an important role in the functional remodeling of the cochlea. Altogether, our data suggest that morphological and functional evolution could be attained through molecular changes affecting both coding and noncoding regulatory regions.